A case study of interreligious learning and teaching in a Catholic primary school – a nexus of leadership, pedagogy, identity, and relationships. Issue 2 (3rd July 2022) - Foley, Toni; Dinan-Thompson, Maree; Caltabiano, Nerina
Abstract : Australia is a religiously diverse nation with a growing trend in 'no religious affiliation' and irrelevance of religion in the lives of young learners and their families. The purpose of this study is to explore the perspectives of School leaders, teachers, and support officers in describing their role in interreligious learning and teaching in the context of one school. Whilst this is a study of one context, the Enhancing Catholic School Identity (ECSI) data and Australian Council for Education Research (ACER) school review data indicate it is a high functioning school. Fourteen one-to-one interviews were transcribed, analysed, and coded revealing themes that clarify key features of the data guided by the research question. Leadership, diversity, relationships, pedagogy, learners, and religious identity emerged as key themes. Delving deeply into the perceptions of the school staff in relation to their engagement in interreligious learning and teaching may offer some insight for other contexts endeavouring to increase the relevance and plausibility of religion in the lives of learners.